Endophyte species influence the biomass production of the native grass Achnatherum sibiricum (L.) Keng under high nitrogen availability. Issue 23 (10th November 2016) - Li, Xia; Zhou, Yong; Mace, Wade; Qin, Junhua; Liu, Hui; Chen, Wei; Ren, Anzhi; Gao, Yubao
Abstract: Research on the interaction of endophytes and native grasses normally takes infection status into account, but less often considers the species of endophyte involved in the interaction. Here, we examined the effect of endophyte infection, endophyte species, nitrogen availability, and plant maternal genotype on the performance of a wild grass, Achnatherum sibiricum . Six different Epichloë ‐infected maternal lines of A . sibiricum were used in the study; three lines harbored Epichloë gansuensis ( Eg ), while three lines harbored Epichloë sibirica ( Es ). These endophytes are vertically transmitted, while Eg also occasionally produces stromata on host tillers. We experimentally removed the endophyte from some ramets of the six lines, with the infected (E+) and uninfected (E−) plants grown under varying levels of nitrogen availability. Eg hosts produced more aboveground biomass than Es hosts only under high nitrogen supply. Endophyte species did not show any influence on the maximum net photosynthetic rate ( P max ), photosynthetic nitrogen use efficiency, or total phenolics of A. sibiricum under all nitrogen conditions. However, the plant maternal genotype did influence the P max and shoot biomass of A . sibiricum . Our results show that endophyte species influenced the shoot biomass of A. sibiricum, and this effect was dependent on nitrogen supply. As with most coevolutionary interactions, A. sibiricum that harbored Eg and Es may show pronounced geographic variation in natural habitats with increased nitrogen deposition. In addition, stroma‐bearing endophyte ( Eg ) provides positive effects (e.g., higher biomass production) to A. sibiricum plants during the vegetative growth stage. Abstract : Our results demonstrate that endophyte species influenced shoot biomass of Achnatherum sibiricum, and this effect was independent of nitrogen supply. In addition, the stroma‐bearing endophyte (Epichloë gansuensis) provides positive effects (e.g., higher biomass production) to A. sibiricum plants during vegetative growth stage.